The efficacy of colchicine in the management of coronavirus disease 2019 - Mohamed Nabil Elshafei (9960500) (2020)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-COV2) infection is a recently emerged viral infection causing predominantly mild upper respiratory symptoms. However, in some instances, it might result in acute respiratory distress syndrome (ARDS) that poses a significant mortality risk. ARDS is postulated to be mediated by a surge of pro-inflammatory cytokines and chemokines, leading to a dysregulated hyper inflammatory response. Colchicine being an anti-inflammatory agent, might mitigate this dysregulated response. Thus, in the absence of therapeutic options available to manage coronavirus disease 2019 (COVID-19), it is imperative to ascertain the effect of colchicine on improving outcomes in COVID-19 patients. Method We will perform a systematic review including a search of the following databases: PubMed, EMBASE, MEDLINE, Clinicaltrials.gov, Cochrane library, and google scholar since inception. We will include randomized controlled trials exploring the effect of colchicine on the efficacy and safety outcomes of COVID-19 patients. Subsequently, we will perform a meta-analysis utilizing the random-effects to ascertain the effect of colchicine on reducing COVID-19 related mortality (primary endpoint) and other efficacy and safety outcomes. Results Our review results are anticipated in early 2021 (based on the completion of several ongoing randomized controlled trial). Our review results will be published in a peer-reviewed journal. Conclusion This systematic review and meta-analysis, is exploring the effect of colchicine on the efficacy and safety outcomes of COVID-19 patients. If colchicine proved to be effective, it would be a significant milestone in the management of COVID-19, a disease with limited available therapeutic options. PROSPERO registration number CRD42020191086 Other Information Published in: Medicine License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1097/md.0000000000021911